Unique Solution for a General Coupled System of Fractional Differential Equations (Journal of Nonlinear Modeling and Analysis, 2024)
This paper discusses a new coupled system of Riemann-Liouvillefractional differential equations, in which the nonlinear terms include theRiemann-Liouville fractional integrals and the boundary value problems involve three-points. We seek also for the existence and uniqueness of solutionsfor this new system. We first get some useful properties of the Green’s function generated by the system, and then we apply a fixed point theorem ofincreasing $φ$-$(h, e)$-concave operators to this new coupled system. Finally, wegain the existence and uniqueness results of the solution for this problem. Inthe end, a concrete example is structured to illustrate the main result.